2021
DOI: 10.5194/acp-21-239-2021
|View full text |Cite
|
Sign up to set email alerts
|

African dust particles over the western Caribbean – Part I: Impact on air quality over the Yucatán Peninsula

Abstract: Abstract. On a global scale, African dust is known to be one of the major sources of mineral dust particles, as these particles can be efficiently transported to different parts of the planet. Several studies have suggested that the Yucatán Peninsula could be influenced by such particles, especially in July, associated with the strengthening of the Caribbean low-level jet. Although these particles have the potential to significantly impact the local air quality, as shown elsewhere (especially with respect to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 105 publications
1
15
0
Order By: Relevance
“…Overall, important differences in elemental composition are evident in the aerosol particles collected in January, April, and July in the Yucatán Peninsula, corroborating the presence of MA, BB, and AD particles as suggested by previous studies (e.g., Yokelson et al, 2009;Kishcha et al, 2014;Ríos and Raga, 2018;Ladino et al, 2019;Raga et al, 2021;Trujano-Jiménez et al, 2021;Ramírez-Romero et al, 2021). Figure 6 shows the average aerosol size distributions sampled under the influence of the different air masses: MA (cyan), BB (red), and AD (yellow).…”
Section: Chemical Composition Vs Air Masssupporting
confidence: 82%
See 4 more Smart Citations
“…Overall, important differences in elemental composition are evident in the aerosol particles collected in January, April, and July in the Yucatán Peninsula, corroborating the presence of MA, BB, and AD particles as suggested by previous studies (e.g., Yokelson et al, 2009;Kishcha et al, 2014;Ríos and Raga, 2018;Ladino et al, 2019;Raga et al, 2021;Trujano-Jiménez et al, 2021;Ramírez-Romero et al, 2021). Figure 6 shows the average aerosol size distributions sampled under the influence of the different air masses: MA (cyan), BB (red), and AD (yellow).…”
Section: Chemical Composition Vs Air Masssupporting
confidence: 82%
“…Although 2018 was a more active AD season than 2017, as characterized by higher PM 2.5 and PM 10 concentrations (Ramírez-Romero et al, 2021), the INP concentrations measured in 2018 in the Yucatán Peninsula were lower than values reported elsewhere. For example, Ardon-Dryer and Levin (2014) found that the INP concentrations in the eastern Mediterranean ranged between 0.16 and 234 L −1 at temperatures between −11.8 and −28.9 • C, and larger values (up to 10 3 L −1 ) at temperatures from −18 to −29 • C were reported by Reicher et al (2019). Price et al (2018) found that in Cape Verde, the INP concentrations were an order of magnitude higher (0.1 and 10 2 L −1 at temperatures from about −10 to −25 • C) than those measured in Sisal and Mérida.…”
Section: Inp Concentration Vs Air Massmentioning
confidence: 56%
See 3 more Smart Citations